Pengaruh Model Pembelajaran Berbasis Masalah PBL dengan Pendekatan Deep Learning terhadap Kemampuan Berpikir Kritis Mata Pelajaran Pendidikan Pancasila Materi Norma Peserta Didik Kelas IV SD Negeri 007 Samarinda Ilir - Dewi Sarah Bumbungan; Makmun; Muhlis; Iksam; Chani Octa (Mataram University, 2026)
Critical thinking is one of the essential competencies that students need to compete in the global era. One effective way to develop this competency is by implementing an appropriate learning model integrated with a relevant instructional approach. This study aimed to examine the effect of the Problem-Based Learning (PBL) model assisted by the Deep Learning approach on the critical thinking skills of fourth-grade students in learning norms within the Pancasila Education subject at SD Negeri 007 Samarinda Ilir during the 2025/2026 academic year. The study employed a quantitative approach using a quasi-experimental method with a nonequivalent control group design. The research participants consisted of an experimental class that received instruction through the Problem-Based Learning model integrated with the Deep Learning approach and a control class that received conventional instruction. The research instrument was a validated critical thinking skills test. The findings revealed a significant effect of implementing the Problem-Based Learning model with the Deep Learning approach on students' critical thinking skills. This was supported by the hypothesis testing result, which showed a significance value of 0.000 (< 0.05), indicating that the null hypothesis (H₀) was rejected and the alternative hypothesis (H₁) was accepted. Furthermore, the experimental class achieved a higher mean score than the control class, demonstrating that problem-based learning supported by the Deep Learning approach creates active and meaningful learning experiences while encouraging students to think more critically in understanding the concept of norms. Therefore, it can be concluded that the Problem-Based Learning model integrated with the Deep Learning approach has a positive effect on students' critical thinking skills in Pancasila Education. This learning model is recommended as an alternative instructional strategy to enhance students' active engagement and promote deeper conceptual understanding.